SWOT ANALYSIS ON THE INDEPENDENT ECONOMIC RESILIENCE STRATEGY OF PESANTREN PROGRAM PARTICIPANTS "ONE PESANTREN ONE PRODUCT (OPOP)" WEST JAVA - Fauziah, Fauziah; Atieqoh, Siti; Asnawati, Asnawati; Suhanah, Suhanah; Imansah, Retno Kartini Savitaningrum (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This study aims to determine the strengths, weaknesses, opportunities and threats for pesantren in maintaining and developing the business and independent business of pesantren with the SWOT analysis method. This research is a type   of qualitative research involving three Islamic boarding schools that already have independent business products and are members of Islamic boarding schools in the One Pesantren One Product program in the West Java region, namely Pesantren Riyadlul Ulum Wadakwah Condong, Tasikmalaya;Pesantren  Al-Istiqomah Bandung and  Pesantren Al-Ashriyyah Nurul Iman Bogor. The results of this study show that the analysis of the IE SWOT matrix diagram is in the area of Quadrant I, namely Internal Factors (X: 0.46) and External Factors (Y:  0.47).  Thus, the   strategy that can be carried out by West Java OPOP Participant Pesantren is SO (strengths-opportunities), where business managers and pesantren units can utilizing internal strengths in capturing external opportunities, such as increasing product production and sales digitally due to the availability of a free digital market place platform; spacious and accessible.